Brushed fabrics and garments
Patent Information
- Application Number
- JP2026051665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-26
- Filing Date
- 2026-03-26
- Publication Date
- 2026-10-13
AI Technical Summary
【0014】 本発明によれば、衣服として使用した時に、制電性、保温性、および起毛部の耐久性に優れる起毛編地を提供することができる。
Smart Images

Figure 2026165087000007 
Figure 2026165087000008 
Figure 2026165087000009
Abstract
Description
[Technical Field]
[0001] This invention relates to brushed fabrics and garments. [Background technology]
[0002] As people desire a more comfortable life, the demands on textile materials are also increasing, requiring more sophisticated properties. Therefore, there is a great deal of effort being put into improving textile materials to achieve the required level of wearability.
[0003] Generally, comfort in clothing depends on various factors, including the environment and atmosphere in which the material is used. Among these, maintaining an appropriate environment between the garment and the skin—that is, the space inside the garment—is a crucial element directly related to comfort. Within this space inside the garment, factors that influence a person's sense of comfort include temperature and humidity inside the garment. However, the range of temperature and humidity inside the garment in which people can feel comfortable is limited.
[0004] Numerous materials have been proposed to enhance heat retention in autumn and winter clothing. For example, as a material that obtains heat retention by creating an air layer within the fabric through napping or pile, Patent Document 1 discloses a reversible double-sided circular knit fabric composed of napping yarn, a binding yarn, and a base fabric yarn or napping yarn and a binding yarn, characterized in that at least one side of the knit stitch-forming surface made of napping yarn is napping.
[0005] On the other hand, materials with napped or piled surfaces are prone to generating static electricity due to friction, and the discharge of this static electricity when putting on or taking off the garment can cause discomfort to the wearer. In particular, the problem of static electricity generation becomes more pronounced when worn in the low humidity and low temperature environments of winter, so materials with excellent antistatic properties that can suppress the generation of static electricity have been proposed.
[0006] For example, Patent Document 2 describes an electrical resistivity of 10 to 10 6Antistatic clothing with excellent aesthetics and antistatic properties has been proposed, consisting of a fabric made by knitting conductive yarn with a density of Ω·cm so that the conductive yarn is exposed on both the front and back surfaces, or a fabric in which the loops of conductive yarn knitted to form loops on both the front and back surfaces are cut and then brushed.
[0007] Furthermore, Patent Document 3 proposes a durable antistatic fabric made by attaching an antistatic agent, such as a surfactant or conductive metal, to a yarn containing antistatic fibers made of antistatic or conductive fibers. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] Japanese Patent Publication No. 2000-256945 [Patent Document 2] Japanese Patent Publication No. 2003-20549 [Patent Document 3] Japanese Patent Publication No. 2009-256858 [Overview of the Initiative] [Problems that the invention aims to solve]
[0009] The double-sided circular knitted fabric described in Patent Document 1 maintains the lightweight bulkiness and heat retention properties of a brushed product while also being superior in quality and physical properties. Furthermore, because it is a knitted fabric with a multi-layer structure, the durability of the brushed portion is excellent. On the other hand, because this knitted fabric uses polyester fibers with low moisture absorption, the antistatic properties of the knitted fabric were sometimes insufficient.
[0010] The antistatic clothing described in Patent Document 2 uses conductive yarn in which a polymer containing a high concentration of metal compounds dispersed as fine particles is placed in the core of a core-sheath type composite fiber. Therefore, non-conductive polymer molecules present between the conductive fine particles inhibit conductivity, resulting in insufficient antistatic properties during winter when static electricity is easily generated. Furthermore, when forming a napped area, loops are formed on both the front and back surfaces of the fabric using pile fibers, and the ends of these loops are cut to create the nap. However, the napped yarn can fall off the knitted fabric, resulting in poor durability of the napped area.
[0011] The durable antistatic fabric described in Patent Document 3 can eliminate static electricity using conductive fibers and an antistatic agent. However, when applying this technology to a napped material to improve heat retention, it is difficult to uniformly apply the antistatic agent to the napped material. Furthermore, although it includes a core-sheath type composite fiber in which a polymer with a high concentration of metal compounds is placed in the core as the conductive fiber, non-conductive polymer molecules present between the metal compounds inhibit conductivity. Therefore, the antistatic properties of the core-sheath type composite fiber and the fabric using it are insufficient, and static electricity is easily generated in winter.
[0012] The present invention aims to solve the above-mentioned problems and provides a brushed knit fabric that is excellent in terms of antistatic properties, heat retention, and durability of the brushed portion when used as clothing. [Means for solving the problem]
[0013] After extensive research, the inventors have found that the following configuration solves the above problem. (1) A napped knitted fabric having a napped portion of fibers on at least one side, wherein the yarn forming loops on one side and the yarn forming loops on the other side are different yarns, and a portion of the knitted fabric contains hygroscopic fibers. (2) The napped knit fabric according to (1), wherein the moisture-absorbing fibers are napped. (3) The napped knit fabric according to (1) or (2), wherein the hygroscopic fiber is a sea-island composite fiber, and a hygroscopic polymer is arranged in the island component in the cross-section of the fiber. (4) The raised knitted fabric according to (3), wherein in the fiber cross section of the sea-island composite fiber, the number of island portions is 2 or more and 12 or less. (5) The raised knitted fabric according to (4), wherein in the fiber cross section of the sea-island composite fiber, the ratio L / R of the radius L of the circumscribed circle with the smallest diameter that encloses all the island portions to the fiber radius R is 0.5 or more and 0.7 or less. (6) The raised knitted fabric according to (4) or (5), wherein in the fiber cross section of the sea-island composite fiber, the ratio I / C of the area I of the island portions to the area C of the circumscribed circle with the smallest diameter that encloses all the island portions is 0.5 or more and 0.9 or less. (7) The raised knitted fabric according to any one of (4) to (6), wherein in the fiber cross section of the sea-island composite fiber, the ratio S / L of the average minimum distance S between adjacent island portions to the radius L of the circumscribed circle with the smallest diameter that encloses all the island portions in the fiber cross section is 0.05 or more and 0.50 or less. (8) A garment comprising the raised knitted fabric according to any one of (1) to (7). [Advantageous Effects of the Invention]
[0014] According to the present invention, it is possible to provide a raised knitted fabric that is excellent in antistatic properties, heat retention, and durability of the raised portion when used as a garment. [Brief Description of the Drawings]
[0015] [Figure 1] It is a model diagram of a cross section in the course direction for explaining the configuration of the present embodiment. [Figure 2] It is a model diagram of a cross section in the course direction of a single-sided raised knitted fabric that is an example of the present embodiment, and a scanning electron microscope image. [Figure 3] It is a model diagram of a cross section in the course direction of a single-sided raised knitted fabric that is an example of the present embodiment. [Figure 4] It is a model diagram of a cross section in the course direction of a double-sided raised knitted fabric that is an example of the present embodiment. [Figure 5] In the present embodiment, it is an example of a schematic diagram showing a cross section of a sea-island composite fiber for explaining the circumscribed circle with the smallest diameter enclosing the island portions and the minimum distance between adjacent island portions. [Figure 6]In this embodiment, this is an example of a schematic diagram showing a cross-section of a sea-island composite fiber to illustrate the arrangement of the island portions. [Modes for carrying out the invention]
[0016] The napped knitted fabric of the present invention is a napped knitted fabric having a napped portion of fibers on at least one side, wherein the yarn forming loops on one side and the yarn forming loops on the other side are different yarns, and a portion of the knitted fabric contains hygroscopic fibers. Preferred embodiments of the present invention will be described in detail below, but the present invention is not limited to these embodiments.
[0017] <Brushed knit fabric> The napped knit fabric of the present invention has a napped portion of fibers on at least one of its surfaces. Here, the napped portion refers to the part of the napped knit fabric where the looped yarn has been napped. The fibers that make up the napped portion are called napped yarns.
[0018] The brushed knit fabric of the present invention is characterized by the use of different yarns to form loops on one side and different yarns to form loops on the other side. Here, "loops" refers to knit loops, tuck loops, and sinker loops that constitute the structure of a particular side. Furthermore, "different yarns to form loops on one side and different yarns to form loops on the other side" means that the yarn that forms loops on one side does not form loops on the other side, but rather the loops are formed by a different yarn.
[0019] To clarify the structure of the loops in the brushed knit fabric of the present invention, we will explain it using Figure 1. Note that Figure 1 uses yarn that is not brushed in order to explain the structure.
[0020] Figure 1(a) schematically shows the stitch shape for one course in a course-direction cross-section of a knitted fabric where "the yarns forming loops on one surface are different from the yarns forming loops on the other surface." In the knitted fabric of Figure 1(a), one surface is composed of knit loops 1a, and the other surface is composed of knit loops 1b, and the yarns forming knit loops 1a and knit loops 1b are different yarns. In addition, in the knitted fabric of Figure 1(a), the yarn forming knit loops 1b forms tuck stitches 2 on the surface where another yarn forms knit loops 1a, but these tuck stitches are for connecting the surface composed of knit loops 1a and the other surface composed of knit loops 1b, and are not included in the loops that constitute the structure of a particular surface.
[0021] Next, Figure 1(b) schematically shows the stitch shape of one course in the course direction cross-section of a single circular knitted fabric, and is composed of knit loop 1, sinker loop 3, and tack loop 4. In the knitted fabric of Figure 1(b), one side is composed of knit loop 1 and tack loop 4, and the other side is composed of sinker loop 3, and knit loop 1, sinker loop 3, and tack loop 4 are formed from the same yarn. Also, Figure 1(c) schematically shows the stitch shape of a rib knit, and one side of the knitted fabric is composed of knit loop 1c, and the other side is composed of knit loop 1d, and are formed from the same yarn. In the case of the knitted fabrics of Figures 1(b) and (c), the yarn forming the loops on both sides of the knitted fabric is the same yarn, and it is not a knitted fabric in which the yarn forming the loops on one side and the yarn forming the loops on the other side are different yarns, as in the present invention.
[0022] As illustrated in Figure 1(a), the brushed knit fabric of the present invention is constructed such that "the yarn that forms loops on one side is different from the yarn that forms loops on the other side." As a result, the yarn that forms loops on one side does not form loops on the other side and is constrained to the fabric by the yarn on the other side. This makes it less likely for the yarn to fall out of the fabric, especially when one side is a brushed area, improving the durability of the brushed area. Furthermore, the mechanical properties of the fabric are improved, resulting in a brushed knit fabric with excellent practicality. Moreover, the gap between one side and the other side can be widened, suppressing air convection within the fabric and improving the heat retention of the fabric.
[0023] As an example of a preferred embodiment of the present invention, Figure 2 shows the cross-sectional structure in the course direction of a napped knit fabric made of three types of yarn. Figure 2(a) schematically shows the stitch shape, and Figure 2(b) shows a scanning electron microscope image. In this embodiment, the napped knit fabric has a base yarn 5, a binding yarn 6, and a napped yarn 7. Here, the base yarn refers to the yarn that is not napped among the yarns exposed on either surface of the napped knit fabric. The binding yarn refers to the yarn that is placed inside the napped yarn, as will be described later. In the napped knit fabric shown in Figure 2, the napped yarn 7 forms knit loops on one surface of the napped knit fabric. On the other surface, knit loops are formed by the base yarn 5. The napped yarn 7 forms tuck stitches on the surface where knit loops are formed by the base yarn 5, but as explained in Figure 1(a), these tuck stitches are for connecting the surface where knit loops are formed by the base yarn 5 and the surface where knit loops are formed by the napped yarn 7, and are not tuck loops themselves. Furthermore, the base yarn 5 does not form loops on the surface where the napped yarn 7 forms knit loops. In addition, on the inside of the knit loops made by the napped yarn 7, knit stitches made by the binding yarn 6 are formed in a similar shape.
[0024] In the brushed knit fabric of the present invention, as shown in Figure 2, it is preferable that the loops formed by the brushed yarn 7 on the surface composed of the brushed yarn 7 are knit loops. When brushing one surface of the knit fabric, the fibers constituting that surface are cut and pulled out, making the surface of the knit fabric fluffy. It is preferable that the constituent fibers form knit loops, as this makes it easier to pull out the fibers and improves the heat retention of the brushed knit fabric. Furthermore, forming knit loops with the brushed yarn 7 makes it easier to restrain the brushed yarn 7 with the binding yarn 6, as will be described later, and improves the durability of the brushed area. In Figure 2, all of the brushed yarn 7 forms knit loops, but some may be tuck loops.
[0025] In the brushed knit fabric of the present invention, it is preferable to form tuck stitches with the brushed yarn 7 on the surface opposite to the surface composed of the brushed yarn 7. By forming tuck stitches with the brushed yarn 7 on the surface opposite to the brushed surface, the brushed yarn 7 is constrained on both sides of the brushed knit fabric, and in addition, the opportunity for the brushed yarn 7 to be subjected to friction on the surface opposite to the brushed surface is reduced, making it less likely for the brushed yarn 7 to fall off the brushed knit fabric. Furthermore, the surface formed by the ground fabric yarn 5 on the opposite side of the brushed surface makes it possible to obtain a brushed knit fabric with excellent mechanical properties for practical use.
[0026] In the brushed knit fabric of the present invention, it is preferable to form knit stitches with a similar shape using a retaining yarn 6 inside the knit loops made of brushed yarn 7. The presence of the retaining yarn 6 inside the knit loops made of brushed yarn 7 restrains the brushed yarn 7 from the inside, thereby suppressing the shedding of the brushed yarn 7 from the brushed knit fabric and improving the durability of the brushed area. Therefore, when the brushed knit fabric is used for clothing or the like, shedding due to friction during wear and pilling can be suppressed. By adjusting the number of brushing cycles, etc., a brushed knit fabric can be formed using only the base yarn 5 and brushed yarn 7 without using the retaining yarn 6, as shown in the cross-sectional structure of the brushed knit fabric in the course direction in Figure 3.
[0027] In the brushed knit fabric of the present invention, the loop shape of the ground fabric yarn 5 that constitutes the other side opposite to the side composed of the brushed yarn 7 may be either knit or tucked, and is not limited to any combination. However, from the viewpoint of obtaining a brushed knit fabric with excellent mechanical properties for practical use, it is preferable to form knitted loops.
[0028] The brushed knitted fabric of the present invention may have a brushed portion on either one or both sides of the fabric. As another example of an embodiment of the brushed knitted fabric of the present invention, Figure 4 shows a form in which both sides of the fabric are brushed. In the brushed knitted fabric shown in Figure 4, one side of the brushed knitted fabric is made up of brushed yarn 7a forming knit loops, and the other side is made up of brushed yarn 7b forming knit loops. Furthermore, the brushed yarn 7a forms tuck stitches on the side in which the brushed yarn 7b forms knit loops, and the brushed yarn 6a forms knit stitches of a similar shape inside the knit loops made by the brushed yarn 7a. Similarly, the brushed yarn 7b forms tuck stitches on the side in which the brushed yarn 7a forms knit loops, and the brushed yarn 6b forms knit stitches of a similar shape inside the knit loops made by the brushed yarn 7b. In other words, the brushed knitted fabric shown in Figure 4 has brushed surfaces on which the brushed yarn 7a and brushed yarn 7b form knit loops, i.e., both sides of the fabric.
[0029] The napped knitted fabric of the present invention has a napped portion of fibers on at least one of its surfaces. The napped knitted fabric of the present invention can be in any form, such as when only one surface of the fabric is napped, as shown in Figures 2 and 3, or when both surfaces of the fabric are napped, as shown in Figure 4. Generally, the mechanical properties of napped yarn are lower than those of the base yarn or binding yarn. Therefore, the napped knitted fabric of the present invention is preferable when only one surface is napped, as this results in superior mechanical properties.
[0030] In the brushed knitted fabric of the present invention, the yarn that forms loops on one side and the yarn that forms loops on the other side may be the same in composition (cotton, rayon, polyester, polyamide, etc.), form (long fiber or short fiber, single fiber diameter, fiber length, number of twists, etc.), and structure (single-component fiber, composite fiber, blended yarn, blended yarn, etc.).
[0031] The weight of the brushed knit fabric of this invention is 50 g / m 2 Preferably, the weight of the napped knit fabric is 50g / m. 2 If the brushed fabric is thicker than this, the air layer created by the fibers in the brushed area becomes thicker, improving the heat retention of the brushed fabric. Therefore, the weight of the brushed fabric should be 100g / m 2 The above is more preferable, 150g / m 2 The above is even more preferable. On the other hand, in terms of improving the handling of the napped knit fabric, the weight of the napped knit fabric should be 400g / m. 2 The following are preferable.
[0032] (Moisture-absorbing fibers) The napped knit fabric of the present invention has hygroscopic fibers incorporated into a portion of the napped knit fabric. Here, "incorporated into a portion of the napped knit fabric" means that the hygroscopic fibers are included in at least a portion of the base yarn, binding yarn, or napped yarn. Furthermore, hygroscopic fibers are defined as fibers with a ΔMR, which is a moisture absorption and release parameter, of 2.0% or more. Here, ΔMR is an index of the hygroscopicity of a fiber, and is a physical property indicated by the difference between the moisture absorption rate of the fiber in a high-temperature, high-humidity environment (temperature 30°C, relative humidity 90%) and the moisture absorption rate of the fiber in standard conditions (temperature 20°C, relative humidity 65%). A larger ΔMR indicates a higher ability to hold water in the fiber, meaning that the fiber has high hygroscopicity. If the ΔMR of the fiber is 2.0% or more, the number of water molecules that can be held in the fiber increases. And, as the amount of moisture held in the fiber decreases, the electrical resistivity of the hygroscopic fiber decreases, thus improving the antistatic properties of the fiber. Furthermore, increasing the amount of moisture that can be retained in the fibers increases the amount of heat generated by the heat of water adsorption, thus improving the heat retention of the napped knit fabric. For this reason, a ΔMR of 4.0% or more is more preferable, and 6.0% or more is even more preferable. On the other hand, the larger the ΔMR of the fiber, the more water molecules are retained in the hygroscopic fiber, which may cause a feeling of coldness when in contact with the hygroscopic fiber. For this reason, a ΔMR of 10.0% or less is preferable for hygroscopic fibers.
[0033] In the brushed knit fabric of the present invention, it is preferable that the hygroscopic fibers are brushed. Brushing of hygroscopic fibers means that the hygroscopic fibers are used as brushed yarn, and the hygroscopic fibers are fluffy on the surface of the brushed knit fabric. The fibers that make up the fluffy part of the brushed knit fabric, i.e., the brushed yarn, are cut and become fluffy, and the surface area of the fibers increases. Therefore, when the hygroscopic fibers are brushed, the opportunities for the hygroscopic fibers to come into contact with electrons generated by friction between the brushed knit fabric and other fabric materials or the human body increase, thereby improving the antistatic properties of the brushed knit fabric. In addition, when the hygroscopic fibers are brushed, the opportunities for the hygroscopic fibers to come into contact with water molecules in the air increase, and the fibers are more likely to generate heat due to the heat of adsorption of water molecules. Therefore, the heat retention properties of the brushed knit fabric are improved.
[0034] The type of hygroscopic fiber in the brushed knit fabric of the present invention can be any type, including natural fibers such as cotton, synthetic fibers such as polyester and polyamide, regenerated fibers such as rayon, and semi-synthetic fibers such as acetate. Among these, synthetic fibers are preferable because their hygroscopic properties can be easily controlled.
[0035] When a hygroscopic fiber is a synthetic fiber, it is preferable that the polymer constituting the fiber is a polymer with high hygroscopic properties (hereinafter sometimes referred to as a hygroscopic polymer). On the other hand, when a hygroscopic polymer is used as a fiber, it tends to reduce the rigidity and strength of the fiber. In order to achieve both of these properties, the hygroscopic fiber according to the present invention is preferably a composite fiber containing a hygroscopic polymer and a polymer responsible for the mechanical properties of the fiber.
[0036] The composite morphology of the hygroscopic fibers in the fiber cross-section of the napped knit fabric of the present invention includes, but is not limited to, core-sheath composite fibers and sea-island composite fibers. If the hygroscopic fibers are sea-island composite fibers with hygroscopic polymers as island components, water molecules held in the fiber structure can be localized to the island components, improving antistatic properties. Furthermore, the mechanical strength of the fiber is improved because components other than the hygroscopic polymer are sea components. For this reason, the morphology of the hygroscopic fibers is preferably a sea-island composite fiber in which hygroscopic polymers are island components and polymers other than the hygroscopic polymer are sea components. When such a composite morphology of fiber is used, the hygroscopic polymer is not exposed on the fiber surface, so water molecules incorporated into the hygroscopic polymer are less likely to be released. As a result, the antistatic properties and heat retention of the napped knit fabric are improved.
[0037] In the case of a sea-island composite fiber in which a hygroscopic fiber has a hygroscopic polymer as the island component, it is preferable that the number of islands be between 2 and 12. As mentioned above, fibers containing a hygroscopic polymer component tend to have reduced mechanical strength. If the number of islands in a sea-island composite fiber of a hygroscopic fiber is 2 or more, the second moment of area increases, increasing the rigidity of the hygroscopic fiber and reducing deformation during tension and bending. Therefore, the fibers are less likely to collapse when napped, the napped state of the napped area can be maintained over time, and the heat retention of the napped knit fabric is improved. As the number of islands increases, the interface area between the sea and the islands increases, increasing the opportunities for electrons generated between the hygroscopic polymer and the napped knit fabric to come into contact, improving antistatic properties. Therefore, it is more preferable that the number of islands in a sea-island composite fiber be 3 or more. On the other hand, when comparing under the same conditions for the island composite ratio, the fewer the number of islands, the fewer the number of islands located in the center of the fiber cross-section, making it easier for static electricity generated by friction in the napped knit fabric to come into contact with each island, and thus improving antistatic properties. Therefore, the number of islands in the sea-island composite fiber is preferably 12 or less, more preferably 9 or less, and even more preferably 6 or less.
[0038] In the case of a sea-island composite fiber in which a hygroscopic fiber is composed of a hygroscopic polymer as the island component, it is preferable that the ratio L / R of the radius L of the circumscribed circle with the smallest diameter that encloses all the island portions in the cross-section of the sea-island composite fiber to the fiber radius R is 0.5 or more and 0.7 or less. The circumscribed circle with the smallest diameter that encloses all the island portions in the fiber cross-section is the circumscribed circle 10 in Figures 5(a) and (b), and the radius L is the radius of the circumscribed circle 10. If the L / R of the hygroscopic fiber that is a sea-island composite fiber is 0.5 or more, the island portions will be closer to the outer surface of the fiber. Therefore, the movement of electrons generated in the napped knit fabric and the conduction of heat will not be hindered by the thickness of the sea portions, and the antistatic properties and heat retention properties can be improved. On the other hand, as mentioned above, the hygroscopic polymer in the island portion has a loose fiber structure and is weak against deformation by external forces. Therefore, if it is placed close to the surface layer of the hygroscopic fiber, the fiber may not only be cut during the napping process, but the loose hygroscopic polymer portion may also peel off, causing the fibers in the napping portion to fall off. From this viewpoint, it is preferable that the L / R ratio of the hygroscopic fiber, which is a sea-island composite fiber, is 0.7 or less, as this can suppress the shedding of the hygroscopic fiber during the napping process. Furthermore, if the L / R ratio of the hygroscopic fiber is 0.7 or less, it is possible to suppress the shedding of hygroscopic fibers from the fibers in the napping portion due to friction during wear or washing in the garment made of the napping knit fabric of the present invention, thereby suppressing a decrease in antistatic properties.
[0039] In the case of a sea-island composite fiber in which a hygroscopic fiber has a hygroscopic polymer as the island component, it is preferable that the ratio I / C of the area of the islands to the area C of the circumscribed circle with the smallest diameter that encompasses all the islands in the cross-section of the sea-island composite fiber is 0.5 or more and 0.9 or less. Here, the circumscribed circle with the smallest diameter that encompasses all the islands is the circumscribed circle 10 in Figure 5(a) or (b), and the area C is the area of the circumscribed circle 10. If the I / C in the fiber cross-section of the hygroscopic fiber which is a sea-island composite fiber is 0.5 or more, the distance between the islands becomes shorter, so that multiple islands function as a pseudo-island, and anisotropy does not occur when the fiber comes into contact with static electricity, thus providing antistatic properties corresponding to the ratio of islands, which is preferable. On the other hand, the smaller the I / C in the fiber cross-section of the hygroscopic fiber, the more contact each island can make with the static electricity generated in the napped fabric on all surfaces, improving the antistatic properties. For this reason, an I / C of 0.9 or less is preferable.
[0040] In the case of a sea-island composite fiber in which a hygroscopic polymer is the island component, it is preferable that the ratio S / L, which is the ratio of the average minimum distance S (μm) between islands in the fiber cross-section to the radius L (μm) of the circumscribed circle with the smallest diameter that encloses all islands in the fiber cross-section, is 0.05 or more and 0.50 or less. Here, the minimum distance between islands in the fiber cross-section is the thickness of the sea portion sandwiched between two adjacent islands, as shown by the length of line segment 11 in Figure 5(c), and the average minimum distance S is determined by the method described in the examples. When S / L is 0.05 or more, the thickness of the sea portion sandwiched between two adjacent islands is sufficient, and the presence of multiple islands increases the second moment of area, increasing the rigidity of the hygroscopic fiber. Therefore, the napped state of the napped portion is maintained, and the air layer of the napped portion can be retained, improving the heat retention of the napped knitted fabric. It is more preferable that S / L be 0.10 or more. On the other hand, if the S / L ratio of the sea-island composite fiber is 0.50 or less, the distance between the island portions becomes shorter. As a result, multiple island portions function as a pseudo-island, preventing anisotropy when the fiber comes into contact with static electricity, and resulting in antistatic properties that correspond to the ratio of island portions. For this reason, an S / L ratio of 0.50 or less is preferable for the sea-island composite fiber, and more preferably 0.40 or less.
[0041] When a hygroscopic fiber is a sea-island composite fiber with hygroscopic polymers as island components and the number of islands is three or more, it is preferable that the island arrangement is single. Here, a single island arrangement means that when line segments are drawn from the centroid of any island to the centroids of the two adjacent islands, without intersecting at any points other than the centroids, and a polygon is drawn with the centroids of all the islands as vertices, all the interior angles of that polygon are less than 180°. As an example, Figure 6(a) shows a pentagon with the centroids Gg, Gh, Gi, Gj, and Gk of islands 8g, 8h, 8i, 8j, and 8k connected by line segments, with each centroid as the vertex. The five interior angles in this pentagon are all less than 180°. On the other hand, as shown in Figure 6(b), when island 8m is located at the center of the fiber cross-section, the drawn figure is a pentagon, but the interior angle formed by the line segments Gi-Gm and Gj-Gm is 180° or more. In this case, the island formation is not single-layered. Compared to island formations located near the surface of the fiber cross-section, island formations located in the center of the fiber cross-section require a relatively longer distance for static electricity generated in the napped fabric to travel to the island, which can reduce the antistatic properties relative to the composite ratio of island components. If the island formation in the fiber cross-section of a hygroscopic fiber that is a sea-island composite fiber is single-layered, the antistatic properties will be proportional to the ratio of island formations.
[0042] In the case of sea-island composite fibers in which hygroscopic fibers are composed of hygroscopic polymers, the sea component is not limited, but polyamides, polyolefins, and polyesters are preferred examples. Since polyester generally does not have functional groups in its molecular structure that form strong interactions with water molecules, electrons generated in the napped fabric are easily incorporated into the hygroscopic polymer, improving the antistatic properties of the napped fabric. For this reason, the sea component of sea-island composite fibers is preferably polyester.
[0043] Suitable polyesters include aromatic polyesters such as polyethylene terephthalate (PET), polytrimethylene terephthalate, and polybutylene terephthalate (PBT), as well as aliphatic polyesters such as polylactic acid. Aromatic polyesters have excellent mechanical properties, heat resistance, and handling characteristics during manufacturing. Therefore, the sea component of sea-island composite fibers is preferably aromatic polyester. Examples of the above aromatic polyesters include polymers obtained by condensation polymerization of aromatic dicarboxylic acids and aliphatic diols, aliphatic dicarboxylic acids and aromatic diols, and aromatic dicarboxylic acids and aromatic diols. Among these, aromatic polyesters composed of aromatic dicarboxylic acids and aliphatic diols are preferred, and aromatic polyesters obtained by condensation polymerization of aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 5-sulfisophthalic acid, and 2,6-naphthalenedicarboxylic acid with aliphatic diols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, cyclohexanediol, and diethylene glycol are preferred. When aromatic polyester is used as the marine component of the hygroscopic fiber, the fiber's properties result in high rigidity. As a result, even when napped, the fibers are less likely to collapse, maintaining the napped state of the napped area and retaining the air layer in the napped area, thus improving the heat retention of the napped knit fabric. Furthermore, garments made from the napped knit fabric of the present invention can be made to have a firm and resilient texture. In accordance with the above viewpoint, polyethylene terephthalate copolymerized with an aromatic dicarboxylic acid such as isophthalic acid, 5-sulfoisophthalic acid, or 2,6-naphthalenedicarboxylic acid is more preferable. In addition, from the viewpoint of efficiently transferring water molecules and electrons generated by friction between the napped knit fabric and other fabric materials or the human body to the hygroscopic polymer of the island component, it is even more preferable that the molecular structure of the marine component aromatic polyester has ionic bonding functional groups. For example, polyethylene terephthalate copolymerized with an aromatic dicarboxylic acid having ionic bonding functional groups such as 5-sulfoisophthalic acid is an example.
[0044] In the case of sea-island composite fibers in which hygroscopic fibers are composed of hygroscopic polymers as island components, suitable examples of hygroscopic polymers for use in hygroscopic fibers include polyether esters, polyetheramides, polyetheresteramides, polyamides, thermoplastic cellulose derivatives, and polyvinylpyrrolidone. Among these, polyether esters, polyetheramides, and polyetheresteramides exhibit excellent stability during melt molding and high hygroscopicity. Therefore, using these hygroscopic polymers improves the antistatic properties of napped knit fabrics. In particular, when the sea component of the hygroscopic fiber consists of aromatic polyester, using polyether esters as island components results in excellent affinity between the sea component and the island component, excellent heat resistance of the hygroscopic polymer, and improved mechanical properties of the napped knit fabric.
[0045] A polyether ester is a block copolymer having ester and ether bonds in its polymer structure. Specifically, it is a block copolymer obtained by polycondensation reaction of a polyester-forming component consisting of a dicarboxylic acid and a diol and a polyalkylene glycol component. The combination of the polyester-forming component and the polyalkylene glycol component is not limited, but a preferred example, from the viewpoint of heat resistance of the hygroscopic polymer, is a polyether ester obtained by copolymerizing an aromatic polyester consisting of an aromatic dicarboxylic acid and an aliphatic diol as the polyester-forming component with polyethylene glycol. More preferably, the combination of the polyester-forming component and the polyalkylene glycol component is a polyether ester consisting of highly crystalline polybutylene terephthalate and polyethylene glycol. Because polymers with such combinations have high crystallinity, the elution of the hygroscopic polymer from the fibers of the napped portion is suppressed when washing garments made of the napped knit fabric of the present invention, improving the washing durability in terms of antistatic properties.
[0046] When the hygroscopic fiber is a sea-island composite fiber with a hygroscopic polymer as the island component, and the hygroscopic polymer is a polyether ester copolymerized with polyethylene glycol using an aromatic polyester composed of an aromatic dicarboxylic acid and an aliphatic diol as the polyester-forming component, it is preferable that polyethylene glycol with a number average molecular weight of 3000 g / mol or more and 20000 g / mol or less is copolymerized at a rate of 20% to 80% by mass relative to the mass of the hygroscopic polymer. When polyethylene glycol with a number average molecular weight of 3000 g / mol or more is copolymerized at a rate of 20% by mass or more relative to the mass of the hygroscopic polymer, the polyethylene glycol component is uniformly distributed in the molecular structure of the polyether ester, forming a continuous layer, thereby increasing the electrostatic permeability of the polyether ester and improving the antistatic properties of the napped knit fabric. More preferably, the polyether ester is copolymerized at a rate of 40% by mass or more of polyethylene glycol with a number average molecular weight of 5000 g / mol or more. From the viewpoint of reactivity during the synthesis of the polyether ester and the heat resistance of the obtained polyether ester, the number average molecular weight of polyethylene glycol is preferably 20000 g / mol or less. Furthermore, from the viewpoint of wash durability in terms of antistatic properties, the copolymerization rate of polyethylene glycol is preferably 80% by mass or less relative to the mass of the hygroscopic polymer, as this increases the crystallinity of the hygroscopic polymer.
[0047] When the hygroscopic fiber is a sea-island composite fiber, the composite ratio of sea components to island components is preferably 70:30 to 95:5 in terms of area ratio in the fiber cross-section. If the composite ratio of sea components is 70% or more, the rigidity of the fiber increases, making it less likely for the fibers to collapse when napped, and allowing the napped state of the napped area to be maintained. As a result, the air layer in the napped area can be retained, and the heat retention of the napped knitted fabric increases. On the other hand, if the composite ratio of sea components is 95% or less, the antistatic properties and heat retention of the napped knitted fabric improve.
[0048] The single fiber diameter of the hygroscopic fiber used in the napped knit fabric of the present invention is preferably 1 μm or more and 20 μm or less. If the single fiber diameter of the hygroscopic fiber is 1 μm or more, the fiber is less likely to fall over even when napped, the napped state of the napped area can be maintained, and the air layer in the napped area can be retained, thus providing high heat retention in the napped knit fabric. In addition, the rigidity of the fiber increases as the single fiber diameter increases, which suppresses the shedding of fibers in the napped area due to friction when wearing a garment made from the napped knit fabric of the present invention. For this reason, the single fiber diameter of the hygroscopic fiber is more preferably 5 μm or more. On the other hand, if the single fiber diameter of the hygroscopic fiber is 20 μm or less, the flexibility of the garment made from the napped knit fabric of the present invention is not impaired, and a comfortable wearing experience can be obtained. Furthermore, if the single fiber diameter is reduced while the total fineness of the hygroscopic fiber is the same, the total surface area of the fiber increases, which increases the opportunity to come into contact with the static electricity generated in the napped knit fabric, improving the antistatic properties of the napped knit fabric. For this reason, the single fiber diameter of the hygroscopic fiber is more preferably 15 μm or less.
[0049] In the napped knit fabric of the present invention, the intermediate stress elongation in the tensile test of the hygroscopic fibers is preferably 10% or less. Here, the intermediate stress elongation in the tensile test refers to the elongation at which the tensile strength is measured by the method described in the Chemical Fiber Filament Yarn Testing Method (JIS L1013:2010), and the stress is half of the measured tensile strength. If the intermediate stress elongation of the hygroscopic fibers is 10% or less, the rigidity of the hygroscopic fibers is high, and the fibers are less likely to collapse when the hygroscopic fibers are napped. Therefore, the napped state of the napped area can be maintained for a long period, retaining the air layer in the napped area and providing high heat retention in the napped knit fabric. Furthermore, when wearing clothing made from the napped knit fabric of the present invention, shedding of fibers in the napped area due to friction, etc., can be suppressed. More preferably, the intermediate stress elongation of the hygroscopic fibers is 8% or less.
[0050] The base yarn and napped yarn constituting the napped fabric of the present invention may be either filaments or staples. Furthermore, the filaments may be monofilaments or multifilaments. On the other hand, in the case of staples, the cut length and crimp count are not limited.
[0051] The cross-sectional shapes of the fibers used in the base yarn and napped yarn that constitute the napped fabric of the present invention can be a wide variety of shapes, such as circular, flat, Y-shaped, T-shaped, hollow, grid-shaped, and well-shaped.
[0052] In the brushed knit fabric of the present invention, the fiber material is not limited to the above-mentioned hygroscopic fibers being arranged in a part of the brushed knit fabric. On the other hand, if the hygroscopic fibers are brushed, and the composite form in the fiber cross-section of the hygroscopic fibers is a sea-island composite fiber with a hygroscopic polymer as the island component, and the hygroscopic polymer is a polyether ester copolymerized with polyethylene glycol and an aromatic polyester consisting of an aromatic dicarboxylic acid and an aliphatic diol as the polyester forming component, then the fiber used in the brushed knit fabric of the present invention is preferably a polyester fiber. Here, a polyester fiber refers to a single-component fiber or composite fiber containing 50% by mass or more of aromatic polyester and aliphatic polyester. If the sea component of the hygroscopic fiber that is a sea-island composite fiber is an aromatic polyester, then the polyester fiber is preferably an aromatic polyester.
[0053] In the brushed knit fabric of the present invention, by using polyester fibers for the fibers constituting the brushed knit fabric other than the hygroscopic fibers, the static electricity generated in the brushed knit fabric is more easily absorbed by the hygroscopic fibers, as aromatic polyesters generally do not have functional groups in their molecular structure that form strong interactions with water molecules, thereby improving the antistatic properties of the brushed knit fabric. Furthermore, a firm and resilient texture can be obtained in the brushed knit fabric. In addition, when manufacturing the brushed knit fabric of the present invention, the dyeing conditions and heat treatment conditions can be set to those for polyester, resulting in a brushed knit fabric of superior quality.
[0054] In the brushed knit fabric of the present invention, a third fiber material may be included in addition to the hygroscopic fiber and the polyester fiber described above. The third fiber material may be used together with the hygroscopic fiber and / or the polyester fiber described above when manufacturing the brushed knit fabric of the present invention, or it may be used as a composite yarn by pre-blending it with the hygroscopic fiber and / or the polyester fiber described above, and is not limited to these.
[0055] If a restraining yarn is included in the napped knit fabric of the present invention, the preferred requirements for the fibers used for the restraining yarn are the same as the preferred requirements for the fiber morphology, cross-sectional shape of the fibers, and polymer constituting the fibers for the base yarn and napped yarn described above.
[0056] The fibers used in the base yarn and brushing yarn that constitute the brushed knit fabric of the present invention have no restrictions on the total fineness when they are in filament form, nor on the yarn count when they are in staple form; however, it is preferable to select them appropriately according to the application and required characteristics. From the viewpoint of using the brushed knit fabric of the present invention as clothing, it is preferable that the total fineness of the fibers used when they are in filament form is 150 dtex or less. By keeping it within this range, the flexibility of the clothing made from the brushed knit fabric of the present invention is not compromised, and a comfortable wearing experience can be obtained. Furthermore, lowering the total fineness of the fibers that constitute the brushed knit fabric results in a more supple knit fabric, so it is more preferable that the total fineness be 100 dtex or less, and even more preferable that it be 75 dtex or less. On the other hand, the lower limit of the total fineness of the fibers used in the base yarn, binding yarn, and brushing yarn that constitute the brushed knit fabric of the present invention is about 4 dtex from the viewpoint of process passability when manufacturing the brushed knit fabric. Furthermore, when the fibers used in the base yarn, binding yarn, and brushing yarn constituting the brushed knit fabric of the present invention are in the form of short fibers, the preferred count can be determined by converting the total fineness in dtex units to metric count, linen count, and cotton count using a known conversion formula. Furthermore, when binding yarn is included in the brushed knit fabric of the present invention, the preferred range of fibers used for the binding yarn is the same as described above.
[0057] The tensile strength of the fibers used in the base yarn and the napped yarn constituting the napped knit fabric of the present invention is preferably 1.5 cN / dtex or higher, from the viewpoint of processability when manufacturing the napped knit fabric.
[0058] The break elongation of the fibers used in the base yarn and brushed yarn constituting the brushed knit fabric of the present invention is preferably 25% to 60% from the viewpoint of processability when manufacturing the brushed knit fabric.
[0059] Furthermore, if the brushed knit fabric of the present invention includes a pressing yarn, the preferred range of fibers used for the pressing yarn is the same as described above.
[0060] <Clothing> The brushed knit fabric of the present invention, when used as a garment fabric, provides garments with excellent antistatic properties, heat retention, and durability of the brushed portion. It is particularly suitable for use as clothing during the winter months when static electricity is easily generated.
[0061] The garment in this embodiment may be either a top or bottom garment. The top may have long sleeves or short sleeves, and the bottom garment may have long hems or short hems. Specific examples of top garments include, but are not limited to, underwear such as inner shirts, general clothing such as shirts as outerwear, cold-weather clothing such as jackets and coats, training wear, sweatshirts, sportswear such as sports shirts, etc. Specific examples of bottom garments include, but are not limited to, general clothing such as slacks, pants, and skirts, sportswear such as sports pants, etc.
[0062] In this embodiment, the garment preferably has the napped surface facing the skin, due to the excellent heat retention of the napped knit fabric of the present invention, which provides comfort during wear, and the excellent antistatic properties that suppress static electricity generated by friction with the human body, etc. On the other hand, it can also be used on the outside of the garment, due to the ability to suppress static electricity generated by friction between the garment made of the napped knit fabric of the present invention and the garment worn on the outside, and due to the excellent durability of the napped portion.
[0063] As described above, garments obtained from the napped knit fabric of the present invention exhibit excellent antistatic properties, particularly in winter when static electricity is easily generated. The antistatic properties in the present invention are evaluated by the "half-life (initial)" measured by the method described in Example M. Half-life is the time (in seconds) it takes for the voltage of a sample to decay to half of its initial voltage after a 10kV voltage is applied to the sample for 30 seconds and the voltage is stopped. The shorter the half-life, the better the antistatic properties of the sample. In this case, for the napped knit fabric of the present invention, it was determined that it has excellent antistatic properties if the half-life (initial) is less than 5 seconds.
[0064] Furthermore, the durability of the antistatic properties when a garment made from the brushed knit fabric of the present invention is repeatedly worn can be evaluated by measuring the "half-life (after 10 washes)" using the method described in Example N. In the case of the brushed knit fabric of the present invention, if the half-life (after 10 washes) is less than 5 seconds, it was determined that the antistatic properties when repeatedly worn are also excellent. In addition, the antistatic properties when a garment made from the brushed knit fabric of the present invention is worn can also be evaluated using the method described in Example Q.
[0065] Garments obtained from the brushed knit fabric of the present invention have excellent heat retention properties. Heat retention in the present invention is evaluated by the "heat retention rate" measured by the method described in Example P. In the brushed knit fabric of the present invention, a heat retention rate of 20% or more was considered to indicate excellent heat retention.
[0066] Garments obtained from the napped knit fabric of the present invention exhibit excellent durability of the napped portion. The durability of the napped portion in the present invention is evaluated by "pilling" measured by the method described in Example O.
[0067] <Method for manufacturing moisture-absorbing fibers> The hygroscopic fibers used in the brushed fabric of the present invention can be obtained by known melt spinning and compound spinning methods. However, the spinning and compounding methods are not limited to those exemplified below.
[0068] The method for producing the marine and island component polymers in the present invention may involve synthesizing the monomers by general polycondensation reactions, addition polymerization reactions, etc., if the raw materials used in production are considered as monomers. The monomers are not limited to petroleum-derived monomers, biomass-derived monomers, mixtures of petroleum-derived monomers and biomass-derived monomers, or recycled monomers obtained by chemical recycling. Alternatively, the polymers may be produced from waste materials such as waste plastics using material recycling methods. Furthermore, in addition to the main component, second and third components may be copolymerized or mixed into the polymers in the present invention, as long as the objectives of the present invention are not departed.
[0069] Methods for producing hygroscopic fibers, which are sea-island composite fibers with hygroscopic polymers as island components, include melt spinning for the purpose of producing long fibers, and solution spinning methods such as wet and wet-dry methods. Among these, melt spinning is preferred from the viewpoint of increasing productivity.
[0070] When using the melt spinning method, the spinning temperature should be set to a temperature at which the polymer species used exhibits fluidity, primarily high-melting-point and high-viscosity polymers. While this fluidity temperature varies depending on the molecular weight, it is preferable to set the temperature between the polymer's melting point and its melting point + 60°C, as this allows for stable production.
[0071] One manufacturing method using melt spinning involves separately melting a marine polymer and a hygroscopic polymer from an island, weighing and transporting them using a gear pump, and forming a composite flow to create a specific composite structure using a known method, which is then extruded from a spinneret. The extruded yarn is cooled to room temperature by blowing cooling air onto it using a yarn cooling device such as a chimney, and then lubricated and bundled using an oil supply device. The bundled yarn is then entangled using a fluid entanglement nozzle device and passed through a take-up roller and a draw-out roller. During this process, the yarn is drawn according to the ratio of the peripheral speeds of the take-up roller and the draw-out roller. Furthermore, the yarn is heat-set by the draw-out roller and then wound up with a winder (winding device). Another method involves setting the peripheral speeds of the take-up roller and the draw-out roller to the same speed, and then winding the yarn with a winder at the same speed to create an undrawn yarn, which is then drawn in a separate process.
[0072] In the hygroscopic fibers used in the brushed knit fabric of the present invention, it is preferable to set the melt viscosity ratio of the two polymers (melt viscosity of the polymer with high melt viscosity / melt viscosity of the polymer with low melt viscosity) to less than 5.0, as this allows for the stable formation of a composite polymer flow and the acquisition of fibers with a good composite cross-section. Here, the melt viscosity of the polymers is the value obtained when measured by the method described in the examples.
[0073] When manufacturing the hygroscopic fibers used in the brushed knit fabric of the present invention, it is difficult to control the composite cross-sectional shape as described above with conventional composite die-cutting nozzles, and it is preferable to use the composite die-cutting nozzle described in Japanese Patent Publication No. 2011-208313.
[0074] In the production of hygroscopic fibers used in the napped knit fabric of the present invention, the spinning draft, expressed by the ratio of the spindle discharge rate to the take-up roller speed (take-up roller speed / spindle discharge rate), is preferably 10 or more and less than 300. The spindle discharge rate referred to here is the discharge volume of polymer per unit time discharged from the discharge hole of the composite spindle divided by the cross-sectional area of the spindle discharge hole.
[0075] This spinning draft correlates with the orientation of the fibers that occurs from the time they are extruded from the discharge hole of the composite die until they are cooled and taken up by the take-up roller. The larger the spinning draft, the greater the orientation of the fibers before they are taken up by the take-up roller. As a result, water molecules are continuously arranged in the direction of the fiber axis, improving the antistatic properties of the napped knit fabric. Furthermore, if the composite morphology in the fiber cross-section of the hygroscopic fibers used in the napped knit fabric of the present invention is a sea-island composite fiber with hygroscopic polymers as island components, the hygroscopic polymers of the island components are oriented in the direction of the fiber axis, thus obtaining particularly excellent antistatic properties.
[0076] If the spinning draft is less than 300, the tension on the polymer immediately after extrusion from the composite die can be reduced, suppressing yarn breakage due to excessive tension before it is taken up by the take-up roller. Furthermore, if the spinning draft is 10 or more, sufficient fiber orientation can be obtained, improving antistatic properties. The spinning draft is more preferably 30 or more and less than 150.
[0077] The hygroscopic fibers used in the napped knit fabric of the present invention may undergo post-processing such as false twisting or twisting after the undrawn yarn has been harvested. It is preferable that the hygroscopic fibers have a crimped structure, as this creates voids between the yarn bundles, and the air layer within these voids improves heat retention. Furthermore, the crimping of the fibers generates repulsion, which helps maintain the napped state of the napped area and retains the air layer in the napped area, thus providing high heat retention in the napped knit fabric.
[0078] For example, the method for applying false twist is not particularly limited as long as it is a method commonly used for polyester and the like, but considering productivity, it is preferable to use a friction false twist machine that uses discs or belts.
[0079] To stably impart crimp to hygroscopic fibers through false twisting, it is preferable that the ratio of yarn running tension before and after a friction body such as a disc or belt (before friction body / before friction body) is between 0.8 and 1.2. A ratio of yarn running tension before and after a friction body of 0.8 or higher is preferable because it causes crimp to occur in the hygroscopic fibers, forming voids between the yarn bundles, and improving heat retention due to the air layer within the voids. A ratio of yarn running tension before and after a friction body of 1.2 or lower is preferable because it can suppress the collapse of fibers due to excessive crimping, maintain the napped state of the napped area, and retain the air layer in the napped area, thus obtaining high heat retention in the napped knitted fabric.
[0080] When crimping is imparted to the hygroscopic fibers used in the napped knit fabric of the present invention, it is preferable that the shrinkage recovery rate, which is a crimping characteristic, be 20% or more. Here, the shrinkage recovery rate can be measured by the method described in Example E. A shrinkage recovery rate of 20% or more for the hygroscopic fibers is preferable because it creates voids between the yarn bundles, and the air layer in the voids improves heat retention. In addition, the crimping of the fibers generates repulsion, which can maintain the napped state of the napped area and retain the air layer in the napped area, thus providing high heat retention in the napped knit fabric.
[0081] <How to manufacture brushed knit fabric> The brushed knit fabric of the present invention is a fabric in which the yarns forming loops on one side are different from the yarns forming loops on the other side. The knit structure before brushing can be manufactured using a conventional knitting machine, such as a double-sided circular knitting machine. The gauge and size of the knitting machine used should be selected according to the total fineness of the fibers used and the weight of the brushed knit fabric to be manufactured. Furthermore, the fibers constituting the brushed knit fabric may be supplied to the knitting machine from separate yarn suction ports or from the same yarn suction port. As an example of a method for forming a knit fabric in which the yarns forming loops on one side are different from the yarns forming loops on the other side, the above-mentioned base fabric yarn, binding yarn and brushed yarn are supplied to a double-sided circular knitting machine, and knit loops are formed on one side of the fabric with the brushed yarn and tuck stitches on the other side, and knit stitches are formed in a similar shape inside the knit loops made by the brushed yarn with the binding yarn. Then, a knit fabric is produced in which knit loops made by the base fabric yarn are further formed on the surface where the tuck stitches made by the brushed yarn are formed. In addition to the stitches mentioned above, you may also combine knitting, tucks, and welts.
[0082] In the napped knitted fabric of the present invention, the method of forming the napped area is not limited, but one method is to pass the knitted fabric through a napping process and then through a shearing process. In the napping process, the fibers constituting the knitted fabric are cut and pulled out with a straight or hook-shaped needle, and the surface of the knitted fabric is made fluffy to form the napped area. The number of napping cycles is not constant as it depends on the knitting structure of the fabric and the constituent fiber material, but since napping cuts the fibers and reduces the mechanical properties of the knitted fabric such as tear strength and bursting strength, it is preferable to nap 10 times or less, and more preferably 5 times or less, as fewer napping cycles suppress the reduction in the mechanical properties of the knitted fabric. After forming the napped area in the napping process, the length of the fluff raised in the napping process is uniformly trimmed in the shearing process to adjust the appearance of the napped area. Similar to napping, the mechanical properties of the knitted fabric decrease as the number of shearing cycles increases, so it is preferable to shear 5 times or less. [Examples]
[0083] The present invention will be described in detail with reference to examples, but the present invention is not limited to these examples. The characteristic values in the examples were measured using the following methods.
[0084] A. Melt viscosity of polymers Polymer samples with a moisture content of 300 ppm or less, obtained by vacuum drying, were subjected to a heating furnace set to the same temperature as the spinning temperature. The samples were placed in a "Capillograph" (registered trademark) capillary rheometer manufactured by Toyo Seiki Seisakusho Co., Ltd., melted under a nitrogen atmosphere, and the viscosity was measured by extruding the samples from the capillary at the tip of the furnace while gradually changing the strain rate. Measurements were started after the samples were allowed to remain in the furnace for 5 minutes, with a shear rate of 1216 s². -1 The value at this point was defined as the melt viscosity of the polymer.
[0085] B. Melting point of polymer (T m ) Using a differential scanning calorimeter (DSC) Q2000 manufactured by TA Instruments, a 20 mg polymer sample was heated from 20°C to 280°C at a heating rate of 20°C / min, held at 280°C for 5 minutes, then cooled from 280°C to 20°C at a cooling rate of 20°C / min, held at 20°C for 1 minute, and then heated again from 20°C to 280°C at a heating rate of 20°C / min. The peak temperature of the endothermic peak observed during this process was defined as the melting point. In the case where multiple endothermic peaks were observed, the peak temperature of the highest-temperature endothermic peak was used as the melting point.
[0086] C. Total fiber density and single fiber density The total fineness and filament count of the fibers constituting the napped knit fabric samples were measured according to the method described in JIS L1096:2010 "Testing Methods for Woven and Knitted Fabrics". The measured total fineness was divided by the filament count and rounded to two decimal places to obtain the single fiber fineness.
[0087] D. Tensile strength, elongation, and intermediate stress elongation Fiber samples were measured using the "TENSILON" (registered trademark) UCT-100 measuring instrument manufactured by Orientec Co., Ltd., under the constant-speed elongation conditions specified in the Chemical Fiber Filament Yarn Testing Method (JIS L1013:2010). Elongation was determined from the elongation at the point showing the maximum strength on the tensile strength-elongation curve. Tensile strength was defined as the value obtained by dividing the maximum strength by the fineness. Intermediate stress elongation was determined from the elongation at the point showing 50% of the maximum strength. Measurements were performed 10 times, and the average values were used for tensile strength, elongation, and intermediate stress elongation.
[0088] E. Stretch recovery rate The fiber sample was prepared into a 10-turn skein using a measuring machine with an appropriate tension adjustment device. The treatment temperature was selected according to JIS L1013:2010 Section 6, and moist heat treatment was performed without applying load. Subsequently, the treatment was carried out according to JIS L1013:2010 Section 8.12, and the shrinkage recovery rate was determined.
[0089] F. Radius L of the circumscribed circle Fiber samples were embedded in an embedding agent such as epoxy resin, and images of the fiber cross-section perpendicular to the fiber axis were taken using a scanning electron microscope (SEM) SU1510 manufactured by Hitachi High-Technologies Corporation at a magnification that allowed observation of 10 or more individual fibers. The obtained images were analyzed using the computer software WinROOF manufactured by Mitani Corporation to measure the radius of the circumscribed circle with the smallest diameter that encloses all the islands in the fiber cross-section to three decimal places. The arithmetic mean of the results obtained by performing this operation on 10 randomly selected individual fibers was calculated and rounded to three decimal places to obtain the radius of the circumscribed circle L (μm).
[0090] G. Fiber radius R Similar to step F, images of fiber cross-sections were taken using a scanning electron microscope (SEM). The radius of a single fiber randomly selected from each image was measured in μm to three decimal places. This process was repeated for 10 randomly selected single fibers. The arithmetic mean of the results was calculated and rounded to three decimal places to obtain the fiber radius R (μm). If the fiber cross-section perpendicular to the fiber axis was not a perfect circle, its area was measured, and the fiber radius obtained by converting it to a circle was used.
[0091] H. Average minimum distance S between island portions In the same manner as in Item F, an image of the fiber cross section was captured by SEM, and the captured image was analyzed using WinROOF, thereby obtaining the average minimum distance S between island portions in the fiber cross section.
[0092] In determining the minimum distance between island portions, as shown in Fig. 5(c), an arbitrary island portion 8a was extracted, and an island portion 8b adjacent to the island portion 8a was extracted. Then, a straight line providing the shortest distance from the center of gravity Ga of the island portion 8a to the island portion 8b was drawn, the intersection points with the outer periphery of each island portion were defined as point Da and point Db, respectively, from the side closer to the center of gravity Ga, and the length of the line segment Da-Db was measured to the third decimal place. At this time, if the line segment Da-Db has an intersection with another island portion, the island portion 8b is not regarded as an island portion adjacent to the island portion 8a. Subsequently, an island portion 8c adjacent to the island portion 8a was extracted, and the minimum distance between the island portion 8a and the island portion 8c was measured in the same manner as described above. This operation was performed on arbitrary island portions (8a, 8b, 8c, etc.) included in one single fiber, and the minimum distance between an arbitrary island portion and an adjacent island portion was measured (in the example of Fig. 5(c), 6 points were measured). Further, this operation was similarly performed on three randomly extracted single fibers to measure the minimum distance, and the average value of these minimum distances was defined as the average minimum distance S (μm) between island portions. The average minimum distance S was rounded to the third decimal place.
[0093] I. ΔMR About 1 to 2 g of a fiber sample or a raised knitted fabric sample prepared according to the method described in Section 6 of JIS L0105:2020 "General Rules for Physical Testing Methods of Textile Products" was weighed into a weighing bottle, dried at 110°C for 2 hours, and then the mass was measured, and this mass was defined as w0. Next, the dried fiber sample was held at a temperature of 20°C and a relative humidity of 65% for 24 hours, and then the mass was measured, and this mass was defined as w 65% . Subsequently, the temperature was adjusted to 30°C and the relative humidity to 90%, the fiber sample was held for 24 hours and then the mass was measured, and this mass was defined as w 90% .
[0094] MR1=[(w 65%-w0) / w0]×100···(1) MR2=[(w 90% -w0) / w0]×100···(2) ΔMR = MR2 - MR1 ... (3) At this time, the value calculated using equations (1) to (3) was defined as ΔMR.
[0095] J. Inspector The mass of a napped knit fabric sample cut into 10cm squares was measured, and the area of the fabric (0.01m²) was measured. 2 Divide by ) and round to the first decimal place to obtain the weight (g / m 2 ) was calculated.
[0096] K. Thickness of brushed knit fabric The thickness of five different locations on the brushed knit fabric sample was measured using a thickness measuring instrument, the average value was calculated, and the fabric thickness (mm) was obtained by rounding to two decimal places.
[0097] L. Bulky The fabric thickness (mm) measured in section K is used to calculate the basis weight (g / m²) in section J. 2 Divide by ) and multiply by 1000, then round to the second decimal place to get the bulkiness (cm 3 We calculated / g).
[0098] M. Half-life (initial stage) According to the method described in JIS L1094:2014 "Test Method for Electrostatic Discharge of Woven and Knitted Fabrics," Method A (Half-Life Measurement Method), a 10kV voltage was applied to a napped knitted fabric sample for 30 seconds. The time (in seconds) until the electrostatic charge of the napped knitted fabric sample decreased to half of the initial electrostatic charge after the application was stopped was measured. This time (in seconds) was defined as the initial half-life of the napped knitted fabric sample. If the electrostatic charge of the napped knitted fabric sample decreased to half of the initial electrostatic charge in less than 1 second after the application was stopped, it was recorded as a half-life of less than 1 second (indicated in the table: <1.0). If the electrostatic charge did not decrease to half of the initial electrostatic charge even after 120 seconds had elapsed since the application was stopped, the measurement was stopped (recorded as half-life exceeding 120 seconds (indicated in the table: 120.0<)).
[0099] N. Half-life (after 10 washes) In JIS L1094:2014 "Test Methods for the Electrostatic Properties of Woven and Knitted Fabrics," Section 6.2 (Washing Treatment of Samples), the number of washes was changed to 10, and after washing the napped knit fabric sample, the half-life (after 10 washes) was measured using the method described in Section M.
[0100] O. Pilling (durability of the napped area) The pilling status of napped knit fabric samples was assessed after 5 hours of operation according to Method A (using an ICI type testing machine) of JIS L1076:2012 "Test Method for Pilling of Woven and Knitted Fabrics". The assessment was made in increments of 0.5 from Grade 1 to Grade 5, with Grade 3 or higher being considered a pass (durability of the napped area).
[0101] P. Heat retention rate A sample of the napped knit fabric was left undisturbed for more than 24 hours in a room adjusted to room temperature of 20°C and relative humidity of 65%. The napped knit fabric sample, cut into 20cm squares, was attached to a constant temperature heating element (room temperature + 10°C) of a heat retention tester (KES-F7 THERMO LABO II TYPE (manufactured by Kato Tech Co., Ltd.)), and the heat loss H1 (J / cm) was measured while blowing air at 30cm / second onto the surface of the test piece. 2 The heat loss H2(J / (cm)) was measured. Next, the same measurement was performed on the bare sample after removing the napped knit fabric, and the heat loss H2(J / (cm)) was measured. 2 The time (in seconds) was measured. At this time, the value calculated using equation (4) was defined as the heat retention rate.
[0102] Heat retention rate (%)=(1-H1 / H2)×100...(4) Furthermore, if the heat retention rate was 20% or higher, it was determined to have excellent heat retention properties.
[0103] Q. Wearing evaluation (antistatic properties) A shirt-like garment was created by sewing together a napped knit fabric sample prepared using the method described in the examples, so that the napped layer was on the skin-facing side of the garment.
[0104] Ten subjects were instructed to wear a shirt-like garment made of 100% cotton circular knit fabric as an undergarment, and then to wear the fabricated garment over it. Next, they were moved to a room with a temperature of 20°C and a relative humidity of 40%, and were asked to sit quietly in a chair for 10 minutes. After that, they walked at a pace of 60 steps / minute for 10 minutes, and then the garment made of the napped knit fabric sample was removed. At this time, a score was assigned by each of the 10 subjects: "no stinging at all" was 5 points, "almost no stinging" was 4 points, "slight stinging" was 3 points, "stinging" was 2 points, and "strong stinging, causing pain" was 1 point. The average score of the scores given by each of the 10 subjects was calculated. An average score of 3.0 or higher was considered passing, and an average score of 3.5 or higher was considered excellent.
[0105] (Manufacturing of fiber A) Polyethylene terephthalate copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol (melt viscosity 170 Pa·s, melting point 244°C) was used for the sea portion, and polybutylene terephthalate copolymerized with 50 mass% polyethylene glycol with a number average molecular weight of 8300 g / mol (melt viscosity 50 Pa·s, melting point 217°C) was used for the island portion. At a spinning temperature of 285°C, the sea portion and island portion polymers were melted separately, and then weighed so that the sea-island ratio was 80:20 by mass. The mixture was then fed into a spinning pack incorporating a composite die, and the incoming polymer was discharged from the discharge holes (hole diameter 0.25 mm, number of holes 36) to form a sea-island composite morphology with 3 islands in total. The discharged composite polymer flow was cooled and solidified in a cooling device, and after supplying a water-containing oil agent with an oil supply device, the material was wound up with the peripheral speed of the first roll (take roller) set to 3000 m / min, the peripheral speed of the second roll (draw roller) set to 3000 m / min, and the winding speed of the winder set to 3000 m / min, to obtain undrawn polyester fibers of 126 dtex-36 filaments. Subsequently, the obtained undrawn yarn was processed using a friction-type false twisting machine at a processing ratio of 1.50, a processing speed of 500 m / min, a heater temperature of 150°C, and a tension ratio of 1.1 to obtain false twisted yarn of 84 dtex-36 filaments.
[0106] (Manufacturing of fibers B, C, and D) The sea-island ratio was changed as shown in Table 1, and a false-twisted yarn of 84 dtex-36 filaments was obtained using the same method as for fiber A.
[0107] (Manufacturing of fibers E, F, and G) Polybutylene terephthalate, obtained by copolymerizing polyethylene glycol with number-average molecular weights of 3400 g / mol (fiber E), 20000 g / mol (fiber F), and 1000 g / mol (fiber G) at a mass of 50%, was used as the island portion to obtain a false-twisted yarn of 84 dtex-36 filaments using the same method as for fiber A.
[0108] (Manufacturing of fiber H) A false-twisted yarn of 84 dtex-36 filaments was obtained using the same method as for fiber A, with polybutylene terephthalate copolymerized at 80% by mass of polyethylene glycol having a number-average molecular weight of 8300 g / mol as the island portion.
[0109] (Manufacturing of Fiber I) Polybutylene terephthalate copolymerized at 30% by mass with polyethylene glycol having a number-average molecular weight of 8300 g / mol was used as the island portion to obtain a false-twisted yarn of 84 dtex-36 filaments using the same method as for fiber A.
[0110] (Manufacturing of fiber J) A false-twisted yarn of 84 dtex-36 filaments was obtained using the same method as for fiber A, with a polyether ester amide (PA-PEG, melt viscosity 85 Pa·s, melting point 200°C) containing 44% by mass of polycaprolactam, 6% by mass of terephthalic acid, and 50% by mass of polyethylene glycol with a number average molecular weight of 1450 g / mol as the island portion.
[0111] (Manufacturing of fibers K, L, M, and N) The polymer was extruded from the discharge holes in a manner similar to that of fiber A, resulting in a sea-island composite morphology where the number of islands is 1 and the total number of islands is 1 (fiber K), the number of islands is 5 and the total number of islands is 6 (fiber L, with a double arrangement of islands), the number of islands is 9 and the total number of islands is 12 (fiber M, with a double arrangement of islands), and the number of islands is 14 and the total number of islands is 24 (fiber N, with a double arrangement of islands). This method was used to obtain false-twisted yarn of 84dtex-36 filaments.
[0112] (Manufacturing of fiber O) The island formation was a sea-island composite with 3 island segments and a total of 3 island segments. The arrangement of the island segments was changed so that the C / I and S / L ratios were as shown in Table 2, and a false-twisted yarn of 84dtex-36 filaments was obtained using the same method as for fiber A.
[0113] (Manufacturing of fiber P) By changing the processing conditions as shown in Table 2, false-twisted yarn of 84dtex-36 filaments was obtained using the same method as for fiber A.
[0114] (Manufacturing of fiber Q) In a spinning pack incorporating a composite spinneret, a false-twisted yarn of 84dtex-72 filaments was obtained using the same method as for fiber A, with the discharge holes (hole diameter 0.20 mm, number of holes 72).
[0115] (Manufacturing of fiber®) Polybutylene terephthalate copolymerized with polyethylene glycol having a number average molecular weight of 8300 g / mol at 50% by mass (melt viscosity 50 Pa·s, melting point 217°C) was used for the sea portion, and polyethylene terephthalate copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt and 1.0% by mass polyethylene glycol having a number average molecular weight of 1000 g / mol (melt viscosity 170 Pa·s, melting point 244°C) was used for the island portion. At a spinning temperature of 285°C, the sea portion and island portion polymers were melted separately, and then weighed so that the sea-island ratio was 20:80 by mass. The mixture was then fed into a spinning pack incorporating a composite die, and the incoming polymer was discharged from the discharge holes (hole diameter 0.20 mm, number of holes 36) to form a sea-island composite morphology with 3 islands and a total of 3 islands. The discharged composite polymer flow was cooled and solidified in a cooling device, and after supplying a water-containing oil agent with an oil supply device, the material was wound up with the peripheral speed of the first roll (take roller) set to 2000 m / min, the peripheral speed of the second roll (draw roller) set to 2000 m / min, and the winding speed of the winder set to 2000 m / min to obtain undrawn polyester fibers of 101 dtex-36 filament. Subsequently, the obtained undrawn yarn was processed using a friction-type false twisting machine at a processing ratio of 1.20, a processing speed of 500 m / min, a heater temperature of 120°C, and a tension ratio of 1.0 to obtain false twisted yarn of 84 dtex-36 filament.
[0116] (Manufacturing of fiber S) Polybutylene terephthalate (melt viscosity 240 Pa·s, melting point 222°C) was used as the base material, and a polyester fiber with 118 dtex-36 filaments was obtained in the same manner as fiber A, except that the peripheral speed of the first and second rolls was set to 2500 m / min and the winding speed of the winder was set to 2500 m / min. Subsequently, processing was carried out under the processing conditions shown in Table 2 to obtain a false-twisted yarn with 84 dtex-36 filaments.
[0117] (Manufacturing of fiber T) Polycaprolactam (N6, melt viscosity 160 Pa·s, melting point 220°C) was used for the sea portion, and polyether ester amide (melt viscosity 85 Pa·s, melting point 200°C) containing 44% by mass of polycaprolactam, 6% by mass of terephthalic acid, and 50% by mass of polyethylene glycol with a number average molecular weight of 1450 g / mol was used for the island portion. At a spinning temperature of 270°C, the sea portion and island portion polymers were melted separately, and then weighed so that the sea-island ratio was 80:20 by mass. The mixture was then fed into a spinning pack incorporating a composite die, and the incoming polymer was discharged from the discharge holes (hole diameter 0.20 mm, number of holes 36) to form a sea-island composite morph with 3 islands and a total of 3 islands. The discharged composite polymer stream was cooled and solidified in a cooling device, and after supplying a water-containing oil agent with an oil supply device, the material was wound up with the peripheral speed of the first roll (take roller) set to 4000 m / min, the peripheral speed of the second roll (draw roller) set to 4000 m / min, and the winding speed of the winder set to 4000 m / min, to obtain undrawn polyamide fibers of 97 dtex-36 filament. Subsequently, the obtained undrawn yarn was processed using a friction-type false twisting machine at a processing ratio of 1.15 times, a processing speed of 500 m / min, a heater temperature of 150°C, and a tension ratio of 1.0 to obtain false twisted yarn of 84 dtex-36 filament.
[0118] [Table 1]
[0119] [Table 2]
[0120] (Example 1) As the napped yarn, fiber A was selected; as the binding yarn, a false-twisted yarn made of polyethylene terephthalate copolymerized with 1.5 mol% of 33dtex-12 filament sodium 5-sulfoisophthalate salt and 1.0 mass% of polyethylene glycol with a number average molecular weight of 1000 g / mol was selected; and as the base yarn, a false-twisted yarn made of polyethylene terephthalate copolymerized with 1.5 mol% of 84dtex-72 filament sodium 5-sulfoisophthalate salt and 1.0 mass% of polyethylene glycol with a number average molecular weight of 1000 g / mol was selected.
[0121] Next, using a 20G double-sided circular knitting machine, knit loops were formed on one side of the fabric using napped yarn, and tuck stitches on the other side. Knit stitches were then formed in a similar shape inside the knit loops made of napped yarn using a binding yarn, and knit loops were formed on the surface where the tuck stitches were formed using napped yarn, thereby creating a knitted fabric in which the yarns forming the loops on one side were different from the yarns forming the loops on the other side. The resulting knitted fabric was then scouring, dyed, and heat-treated according to the usual dyeing process for polyester knitted fabrics using cationic dyes. The napped yarn was then raised by applying a napping process and shearing process to the side of the dyed knitted fabric where the knit stitches were formed using napped yarn, thereby obtaining a napped knitted fabric.
[0122] A shirt was sewn using the resulting brushed knit fabric. The evaluation results for the brushed knit fabric and the garment are shown in Table 3.
[0123] (Examples 2-19, Comparative Example 1) In Example 1, the brushed yarn was changed as shown in Tables 3-5, but the brushed knit fabric and shirt were sewn in the same manner as in Example 1. The evaluation results of the brushed knit fabric and the garment are shown in Tables 3-5.
[0124] (Example 20) In Example 1, the brushed knit fabric was prepared and the shirt was sewn in the same manner as in Example 1, except that a retaining thread was not used. The evaluation results of the brushed knit fabric and the wear evaluation results are shown in Table 4.
[0125] (Example 21) Except for selecting a false-twist yarn made of polyethylene terephthalate copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt of 84dtex-36 filaments and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol as the napped yarn, fiber A as the binding yarn, and a false-twist yarn made of polyethylene terephthalate copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt of 84dtex-72 filaments and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol as the base yarn, the napped knit fabric was prepared and a shirt was sewn in the same manner as in Example 1. The evaluation results of the napped knit fabric and the wear evaluation results are shown in Table 5.
[0126] (Comparative Example 2) In Example 1, the napped yarn was made from a false-twisted polyester fiber (ΔMR: 0.1%) of 84dtex-36 filaments, copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol. The napped fabric was prepared and a shirt was sewn in the same manner as in Example 1, except that the napped yarn was a false-twisted yarn of polyethylene terephthalate copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol.
[0127] Due to the low moisture absorption of the knitted fabric, its heat retention was poor. Furthermore, static electricity was generated during testing as a shirt, resulting in an uncomfortable wearing experience.
[0128] (Comparative Example 3) In Example 1, a knitted fabric was created without applying a napping or shearing process to the dyed knitted fabric, and a shirt was sewn from it. As a result, the heat retention of the knitted fabric was low because the moisture-absorbing fibers were not napping.
[0129] (Comparative Example 4) In Example 1, a knitted fabric was prepared using a 20G double-sided circular knitting machine, in which the yarn forming loops on one side of the rib knit and the yarn forming loops on the other side were the same yarn, and then dyed. Subsequently, the knit stitches on one side of the fabric were subjected to napping and shearing processes to create a napping knitted fabric, and a shirt was sewn. The knitted fabric had low heat retention, and the durability of the napping area was also poor.
[0130] (Example 22) As the napped yarn, fiber A was selected, and as the binding yarn, a false-twisted yarn of polyethylene terephthalate copolymerized with 1.5 mol% of 33dtex-12 filament sodium 5-sulfoisophthalate salt and 1.0 mass% of polyethylene glycol with a number average molecular weight of 1000 g / mol was selected.
[0131] Next, using a 20G double-sided circular knitting machine, knit loops were formed on both the surface and skin-facing sides of the fabric using the brushed yarn. Tuck stitches were then formed on the opposite skin-facing side using the brushed yarn that had formed knit loops on the surface, and tuck stitches were then formed on the opposite surface using the brushed yarn that had formed knit loops on the skin-facing side. By forming similarly shaped knit stitches with a binding thread inside the knit loops of each brushed yarn, a fabric was created in which the brushed yarn forming loops on one side was different from the brushed yarn forming loops on the other side. The fabric was then scouring, dyeing, and heat-treated according to the usual dyeing process for polyester knit fabrics using cationic dyes. The brushed yarn was then brushed and sheared on both sides of the resulting dyed fabric to create a brushed knit fabric.
[0132] A shirt was sewn using the resulting brushed knit fabric. The evaluation results for the brushed knit fabric and the garment are shown in Table 6.
[0133] (Comparative Example 5) In Example 22, the brushed yarn was made from a false-twisted polyester fiber (ΔMR: 0.1%) of 84dtex-36 filaments, copolymerized with 1.5 mol% sodium 5-sulfoisophthalate salt and 1.0 mass% polyethylene glycol with a number average molecular weight of 1000 g / mol. The brushed fabric was prepared and a shirt was sewn in the same manner as in Example 22.
[0134] Due to the low moisture absorption of the knitted fabric, its heat retention was poor. Furthermore, static electricity was generated during testing as a shirt, resulting in an uncomfortable wearing experience.
[0135] (Comparative Example 6) In Example 22, a knitted fabric was created without applying a napping or shearing process to the dyed knitted fabric, and a shirt was sewn using this fabric. As a result, the knitted fabric had low heat retention because it was not napping.
[0136] [Table 3]
[0137] [Table 4]
[0138] [Table 5]
[0139] [Table 6]
[0140] The brushed knit fabrics of Examples 1-22 all exhibited excellent antistatic properties, as their initial half-lives were all less than 5 seconds. Furthermore, the brushed knit fabrics of Examples 1-22 also possessed excellent heat retention and superior durability of the brushed areas in pilling evaluations. They also demonstrated excellent static electricity suppression in wear evaluations. Additionally, the brushed knit fabrics other than those of Examples 6, 13, and 17 showed excellent antistatic properties even after repeated wear, as their half-lives remained below 5 seconds after 10 washes.
[0141] On the other hand, in Comparative Examples 1-6, no brushed knitted fabric was obtained that was superior in all aspects: antistatic properties, heat retention, and durability of the brushed portion. [Explanation of symbols]
[0142] 1, 1a, 1b, 1c, 1d knitted loops 2 Tuck stitches 3 Sinker Loop 4 Tack Loops 5 Ground tissue yarn 6, 6a, 6b Binding threads 7, 7a, 7b brushed yarn 8a, 8b, 8c, 8d, 8e, 8f, 8g, 8h, 8i, 8j, 8k, 8m Island 9 Kaifu 10 Circumscribed circle 11. Minimum distance between islands Da is the intersection of a line drawn from the centroid of island 8a toward island 8b and the outer perimeter of island 8a. Db Intersection of the line drawn from the centroid of island 8a toward island 8b with the outer perimeter of island 8b Ga, Gg, Gh, Gi, Gj, Gk, Gm Centroid of the island
Claims
1. A napped knitted fabric having a napped portion of fibers on at least one side, wherein the yarn forming loops on one side and the yarn forming loops on the other side are different yarns, and a portion of the knitted fabric contains hygroscopic fibers.
2. The brushed knit fabric according to claim 1, wherein the moisture-absorbing fibers are brushed.
3. The napped knitted fabric according to claim 1 or 2, wherein the hygroscopic fiber is a sea-island composite fiber, and a hygroscopic polymer is arranged in the island component in the cross-section of the fiber.
4. The napped knitted fabric according to claim 3, wherein the number of island portions in the fiber cross-section of the sea-island composite fiber is 2 or more and 12 or less.
5. The napped knitted fabric according to claim 4, wherein in the fiber cross-section of the sea-island composite fiber, the ratio L / R of the radius L of the circumscribed circle with the smallest diameter that encloses all the island portions to the fiber radius R is 0.5 or more and 0.7 or less.
6. The napped knitted fabric according to claim 4, wherein in the fiber cross-section of the sea-island composite fiber, the ratio I / C of the area I of the island portion to the area C of the circumscribed circle with the smallest diameter that encloses all the island portions is 0.5 or more and 0.9 or less.
7. The napped knitted fabric according to claim 4, wherein in the fiber cross-section of the sea-island composite fiber, the ratio S / L of the average minimum distance S between islands to the radius L of the circumscribed circle with the minimum diameter that encompasses all islands in the fiber cross-section is 0.05 or more and 0.50 or less.
8. A garment made of a brushed knit fabric according to claim 1 or 2.
Citation Information
Patent Citations
Double raising interlock circular knitted fabric
JP2000256945A
Antistatic clothes
JP2003020549A
Durable antistatic fabric
JP2009256858A